Spontaneous Nonaneurysmal Subarachnoid Hemorrhage: Review of 75 Cases - Sharma, Mohan R.; Grant, Gerald A.; Nicoletto, Heather A.; Douville, Colleen M.; Newell, David W. (Nepal Journal of Neuroscience, 2005)
The primary objective of this study was to describe the clinical, radiological, and transcranial Doppler (TCD) ultrasonography characteristics of patients with spontaneous, nonaneurysmal subarachnoid hemorrhage (SNSAH), and analyze their short- term outcome at discharge. The secondary objective was to determine their risk factors for the development of vasospasm. Seventy-five patients with SNSAH were analyzed in terms of clinical, radiological, and TCD parameters, as well as Glasgow Outcome Scale (GOS) at discharge. The patients were then divided into two groups based on whether or not they developed vasospasm by TCD ultrasonography. Twenty of 75 patients (26.7%) had vasospasm by TCD criteria. Age, sex, cigarette smoking, hypertension, clinical Hunt and Hess and World Federation of Neurological Surgeons (WFNS) grading, Fisher’s grade on computerized tomography (CT) scan, or discharge GOS score did not correlate with the development of vasospasm. Hydrocephalus, identified in 11 (14.7%) patients upon admission, was significantly more common in patients with vasospasm (p< 0.0001). Patients with vasospasm stayed in the hospital significantly longer than those without vasospasm (P<0.001). Vasospasm in SNSAH is more prevalent than previously thought. There is no statistical correlation between the incidence of vasospasm in patients with SNSAH and age, sex, smoking, hypertension, and different admission clinical and Fisher’s grades. However, the presence of hydrocephalus at admission correlated significantly with the development of vasospasm. Despite the high incidence of vasospasm, there is no difference in short-term clinical outcome at discharge between the patients with and without vasospasm. Nepal Journal of Neuroscience, Volume 2, Number 1, 2005, page: 59-66